ECG ABNORMALITIES IN ALTERNATING HEMIPLEGIA: A BROADENED PHENOTYPE. Issue 11 (14th October 2015) - Jaffer, Fatima; Avbersek, Andreja; IAHRC,; ENRAH,; Hanna, Michael G; Houlden, Henry; Kaski, Juan P; Cross, Helen; Sisodiya, Sanjay M
Abstract : Introduction: Alternating hemiplegia of Childhood (AH) caused by de novo mutations in ATP1A3, is characterised by recurrent plegic and dystonic episodes, seizures, non-paroxysmal neurological features, and dysautonomia. Premature mortality is observed and attributed to sudden unexpected death in epilepsy. A single case of asystole in AH is reported. Other neuronal channelopathies have cardiac involvement, and since ATP1A3 is expressed in cardiomyocytes, we hypothesised that ECG abnormalities are present in AH. Methods: 52 patients fulfilling the diagnostic criteria for AH were recruited, and screened for ATP1A3 mutations. ECGs were analysed for heart rate, cardiac axis, PR, QRS, RR, and QTc intervals, repolarisation patterns, and J-point abnormalities. Results: 53.8% exhibited abnormal resting 12-lead ECGs independent of seizures or AH episodes; 48.1% had repolarisation abnormalities. The proportion of intraventricular conduction delay or partial right bundle branch block was greater in this cohort compared to the general population. ECG abnormalities were significantly greater in patients >16 years than in those <16 years (p=0.0095), and also within the most common mutation group (D801N; p=0.045). Conclusions: These ECG abnormalities reflect impaired repolarisation reserve in AH in an age-dependent manner, and may account for some cases of premature mortality observed. Long-term cardiac surveillance in AH is recommended.